2019
DOI: 10.1016/j.indmarman.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Institutional means-ends decoupling work in industrial R&D project implementation

Abstract: Managing goals is a key network management function and is critical in the implementation of industrial R&D projects. In this paper, we explore the implementation of an industrial R&D project, focusing in particular upon the role of means-ends decoupling work to understand how the goals are managed. We combine several data sources in our case research to explore project implementation through an understanding of means-ends decoupling work. We collected indepth interviews, archival records and field observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Di Maddaloni and Sabini (2022) introduced the concept of means-end decoupling as a powerful perspective to understand the discrepancy between what project managers perceive to be moral (including communities), versus what project organisations actually do (not including them). Jabbouri et al (2019) identified three types of means-ends decoupling work in R&D project implementation: "work on" causal complexity, "work at" behavioural invisibility, and "work with" practice multiplicity. Despite some recent studies started to emerge looking at, especially, means-end decoupling, there is still a lack of studies looking at project responses in the context of coercive pressures.…”
Section: Decoupling In Construction Projectsmentioning
confidence: 99%
“…Di Maddaloni and Sabini (2022) introduced the concept of means-end decoupling as a powerful perspective to understand the discrepancy between what project managers perceive to be moral (including communities), versus what project organisations actually do (not including them). Jabbouri et al (2019) identified three types of means-ends decoupling work in R&D project implementation: "work on" causal complexity, "work at" behavioural invisibility, and "work with" practice multiplicity. Despite some recent studies started to emerge looking at, especially, means-end decoupling, there is still a lack of studies looking at project responses in the context of coercive pressures.…”
Section: Decoupling In Construction Projectsmentioning
confidence: 99%
“…Many contemporary organizations adopt external practices as a response for institutional pressures (Bromley and Powell, 2012). Such firms would implement cutting edge technological practices, which have an ambiguous links to the firms' core goals (Jabbouri et al, 2019;Wijen, 2014).…”
Section: Ai Readiness Second Component: Pre-identified Strategic Impactsmentioning
confidence: 99%
“…This preliminary process aims at diagnosing the firms' most prevailing business problems, that can be potentially addressed through AI implementation. Organizations should not fall in the trap of adopting AI as a "symbolic action" (Bromley and Powell, 2012), to cope with increasing pressures for being "technology-driven" (Jabbouri et al, 2019).…”
Section: Ai Readiness Second Component: Pre-identified Strategic Impactsmentioning
confidence: 99%
See 2 more Smart Citations